English methods of birth control - Sanger, Margaret, 1879-1966
1915 1915 1910s 18 pages 14 WILL FAMILY RESTRICTIONS HELP THE CAUSE OF LABOUR? There is a general opinion among some people of Europe that the national use of preventive measures will reduce the wages of the working class. They claim that the worker does and will receive wages according to his least amount of subsistence. That if a man has ten children he will have more needs, and therefore demand a higher wage than the man with only two children. We in the United States of America know that a job does not pay according to the size of the family or the man's needs. We know that a man who has a family of ten children does not receive wages above the man with two children. A job or trade pays a maximum standard wage regardless of the size of the applicant's family. In some trades, like the weavers, or piece work where the wage depends upon the individual's output, the man with the large family earns far less because his individual earning capacity is lessened through poverty, less nourishment, poorer home surroundings, lower standards of living, more worry, greater responsibility, more anxiety, than the man with only two children. The man with a large family must bring his standards down to fit the wage his job pays ; if he does not like the price, he can leave it, others will accept it gladly. The working class have produced sufficient slaves to keep the army of the unemployed always ready to accept a job at any price. When men cannot be had cheap enough, woman's labour will do ; child labour is still cheaper. Industry demands profits ; profits demand cheap labour. It has been my experience to find that the average man with a large family is compelled to sell his labour power cheaper than the man with a small family. His family needs are more pressing and more urgent, and he must accept a job at any price. It is the Labour Union which forces him to demand the standard wage, and backs him up in getting it. His urgent needs would soon be taken advantage of by the master class were it not for 15X/2/566/51